Medidas preventivas en salud bucal y su relación con el índice de higiene oral en gestantes del centro de salud de Moronacocha, Iquitos 2022 - Álvarez Arévalo, Juan Diomar (2023)
Objective: To determine the relationship between preventive measures in oral health and the oral hygiene index at the Moronacocha Health Center, Iquitos 2022. Method: The type of study is quantitative, correlational research design, and descriptive research level; where a sample of 50 pregnant women duly registered at the Moronacocha health center was evaluated, applying the research instrument called preventive oral health measures, made up of 22 questions, where 40% of primiparous women and 60% of multiparous women participated. having a high percentage of birth of adolescents and young people. Results: the knowledge about preventive measures of pregnant women is medium 80%, low 16% and high 4%. The oral hygiene index, 44% regular, 28% good and bad oral hygiene respectively. Conclusion: There is a moderate significant relationship between preventive oral health measures and the oral hygiene index in pregnant women at the Moronacocha Health Center (p=value of ? 0.090).